A Causal-Comparative Analysis on the Integration of Bionic Fonts in Science Reading Materials - Sardido, Jason Laruap; Sanico, Andrey Ibarbia; Rubin, John Paul Lebosada; Villarino, Althea Batuigas; Cabahug, Jesyl Aloba; Heredia, Jenalyn Carungay; Cabrillos, Shahanie May; Lati, Aida Marie Bañares; Picardal, Marchee Tabotabo (FKIP Universitas Lampung, 2024)
Abstract: A Causal-Comparative Analysis on the Integration of Bionic Fonts in Science Reading Materials. Objectives: The study aimed to evaluate the effect of Bionic fonts on reading speed and comprehension levels among Filipino 10th grade students. Methods: The study involved 490 Filipino 10th graders, utilizing Mann-Whitney U-tests for quantitative analysis and thematic analysis for student attitudes towards Bionic fonts. Findings: The study found comparable reading speed and comprehension levels in Bionic and Traditional font groups, with most participants categorized as